2016
DOI: 10.3348/kjr.2016.17.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Non-Contrast CT Using Dual-Energy Spectral CT: Feasibility of Coronary Artery Calcium Scoring

Abstract: ObjectiveTo evaluate the feasibility of coronary artery calcium scoring based on three virtual noncontrast-enhanced (VNC) images derived from single-source spectral dual-energy CT (DECT) as compared with true noncontrast-enhanced (TNC) images.Materials and MethodsThis prospective study was conducted with the approval of our Institutional Review Board. Ninety-seven patients underwent noncontrast CT followed by contrast-enhanced chest CT using single-source spectral DECT. Iodine eliminated VNC images were recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
5
34
1
Order By: Relevance
“…Additional conceivable advances in imaging of the coronary arteries with PCD-CT include image noise reduction and decreased radiation dose (28,29). Furthermore, the multi-energy capabilities might help to subtract CAC, and could be beneficial to obtain both a CSCT and CCTA from only one CT scan (135). Moreover, the technique can permit the usage of more than one contrast agent, which may be useful in thoracic imaging.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Additional conceivable advances in imaging of the coronary arteries with PCD-CT include image noise reduction and decreased radiation dose (28,29). Furthermore, the multi-energy capabilities might help to subtract CAC, and could be beneficial to obtain both a CSCT and CCTA from only one CT scan (135). Moreover, the technique can permit the usage of more than one contrast agent, which may be useful in thoracic imaging.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Relative advantages of CACS performed by non‐contrast‐enhanced CT include ease of performance and interpretation, high reproducibility, low cost, and a lack of need for an intravenous contrast agent 61. However, there are important limitations of CACS including that it generally only represents ≈20% of total plaque volume, it cannot be used to determine if there is flow‐limiting stenosis, and it does not provide information on plaque morphology or subtype because of its lower resolution and poor tissue contrast 62.…”
Section: Multimodality Imaging Techniquesmentioning
confidence: 99%
“…Another clinical application is calcium scoring from virtual nonenhanced images created from data acquired during contrast-enhanced CT angiography. The ability to obtain a calcium score without performing a nonenhanced scan reduces the patient's radiation burden (104)(105)(106)(107). Yamada et al (105) demonstrated an excellent correlation between coronary calcium scores obtained with virtual nonenhanced images and those obtained from dedicated nonenhanced images in conjunction with increased SNR and CNR on multi energy CT images; the radiation dose was significantly lower when nonenhanced data were not acquired (4.3 versus 5.4 mSv) (105).…”
Section: Radiation Dose Savingsmentioning
confidence: 99%